Growing Together, Growing Apart - Hanson, Mark S. (Dialog, 2005)
How does diversity define the limits of the Body of Christ in the context of its fundamental unity? For Lutherans the visible unity of the church is grounded in those signs and constitutive elements which convey salvation. Unified on the basis of a common baptism, a common communion, and a common mission, the church of the gospel must be defined more by being than by doing. The church doing God's redemptive work in creation will always experience tension, but we must be mindful that wholeness is not equivalent to sameness.